2016
DOI: 10.1634/theoncologist.2016-0090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oncologists’ Attitudes Toward End-of-Life Care on Patients’ Access to Palliative Care

Abstract: Background. It is unclear how oncologists' attitudes toward end-of-life (EOL) care affect the delivery of care. The present study examined the association between oncologists' EOL care attitudes and (a) timely specialist palliative care referral, (b) provision of supportive care, and (c) EOL cancer treatment decisions. Methods. We randomly surveyed 240 oncology specialists at our tertiary care cancer center to assess their attitudes toward EOL care using a score derived from the Jackson et al. qualitative conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…In our survey, the program name supportive care was used in approximately one‐third of cancer centers. Previous studies have reported that both patients and oncologists are much more willing to refer patients to palliative care earlier in the disease trajectory if supportive care is used instead of palliative care …”
Section: Discussionmentioning
confidence: 99%
“…In our survey, the program name supportive care was used in approximately one‐third of cancer centers. Previous studies have reported that both patients and oncologists are much more willing to refer patients to palliative care earlier in the disease trajectory if supportive care is used instead of palliative care …”
Section: Discussionmentioning
confidence: 99%
“…Discordance in beliefs about curability was less common in dyads involving oncologists who practiced longer. Experienced oncologists may have a higher propensity or comfort level for discussing prognosis, which can help patients understand their illness. It is also possible that older patients are more likely to believe or trust more experienced oncologists .…”
Section: Discussionmentioning
confidence: 99%
“…One study focused on family physicians and highlighted that the use of specific tools for palliative care needs assessment was useful to address those needs in a timely manner [23]. Finally, several of quantitative studies showed that previous experience, general knowledge of end-of-life care, palliative care education provision for HPs (e.g., workshops and practical training) [35,51,52,58,64] as well as clinical guidelines on palliative care delivery [51] led to greater utilization of palliative care services.…”
Section: Awareness Of Palliative Carementioning
confidence: 99%